PHYSICAL ACTIVITIES IN THE 20TH CENTURY ACCORDING TO ERIC HOBSBAWM'S “ERA OF THE EXTREMES (Fiep Bulletin - online, 2012)
This paper makes an interpretation of Physical Education and Sport in the 20th century fromthe perspective of the theoretical reference established by the analysis of the English historian EricHobsbawm.After a general analysis of Physical Education and Sport, the author attempts to correlate theidentified facts with Hobsbawm's historical periods: the Catastrophe Age, The Golden orDevelopment Age (sic) and the Crisis Age, which include the first years of the 21st century.The aspect that is considered most meaningful is related to the Age of the Crisis, when anumber of trends can be identified for the area of Physical Education and Sport. In fact, that is theperiod when the deconstructions and reconstructions in this social field take place.
Keywords: physical education; sport; physical activity; Eric Hobsbawm